Structural, Optical, Dielectric and Magnetic Properties of Double Perovskite Oxides A2FeTiO6 (A = Zn, Mg, Cu) Nanopowders - Ghrib, Taher; Ercan, Filiz; Kayed, T. S.; Flemban, Tahani H.; Yildiz, Mesut; Kaygili, Omer; Ercan, Ismail (Springer Heidelberg, 2022)
The investigation of structural, microstructural, optical, dielectric, and magnetic properties of double perovskite materials Zn2FeTiO6 (M1), Mg2FeTiO6 (M2), and Cu2FeTiO6 (M3) synthesized by solid-state reaction was reported in this work. The three compounds crystalized in a monoclinic structure with the space group of P12(1)/c. The microstructure of M1, M2, M3 samples was scanned by SEM to show the crystallinity in shape, and elemental mappings from EDX confirmed the consistency with sample concentrations. Similar spectra were observed from the FTIR technique. The diffused reflectance in the 200-800 nm wavelength range and photoluminescence for the samples were measured to investigate the optical properties. Dielectric constants, conductivity, frequency dependence of the tangent loss (tan delta), AC conductivity at different dc bias voltages, and the electric modulus M(omega) were examined to ensure the potential of the examined materials for microelectronic applications in circuit devices.
Keywords: (Zn; Mg; Cu)(2)FeTiO6; Double perovskite oxide; Dielectric loss; Electric modulus; Photoluminescence